Effects of Smoking on Diabetic Nephropathy - Gündoğdu, Yasemin; Anaforoğlu, İnan (Frontiers in Clinical Diabetes and Healthcare, 2022)
Diabetes is a systemic metabolic disease with serious complications that cause significant stress on the healthcare system. Diabetic kidney disease is the primary cause of end stage renal disease globally and its progression is accelerated by various factors. Another major healthcare hazard is tobacco consumption and smoking has deleterious effects on renal physiology. Prominent factors are defined as sympathetic activity, atherosclerosis, oxidative stress and dyslipidemia. This review aims to enlighten the mechanism underlying the cumulative negative effect of simultaneous exposure to hyperglycemia and nicotine.